Competing with computers: An integrated approach to identifying areas of competitive advantage - R. T. Watson; L. F. Pitt (South African Journal of Business Management, 1989)
The potential for information systems technology (IST) to afford competitive advantages to organizations which exploit it effectively has been well documented. However, there has not been a great deal of work in the area of how managers can identify opportunities for the strategic use of IST. Three broad approaches have been outlined for the identification of these opportunities, namely brainstorming, case studies, and conceptual models. The authors present an overview of these approaches and then suggest their integration in a process model which should lead to synergy in strategy teams charged with the identification of strategic uses of IST.
Keywords: 650